Experimental study on ecofriendly and sustainable aeolian sand bricks with microbial-induced calcite precipitation technology - Xu, Yeshou; Shah, Syed Ahmad Ali; Mao, Minhui; Ding, Feng-Ying; Guo, Ying-Qing; Huang, Xinghuai; Zhang, Tianzhu; Shahzada, Khan (Frontiers in Materials, 2026)
Desertification persists as a significant global environmental and economic challenge, with one promising mitigation strategy involving the utilization of desert aeolian sand in engineering applications. This approach not only aids in rehabilitating degraded landscapes but also contributes to reducing CO2 and dust emissions associated with conventional construction materials. It also investigates the application of microbial-induced calcium carbonate precipitation (MICP) technology to enhance soil consolidation and improve the mechanical properties of sand bricks. Specifically, the NH4-Ye medium at pH 9 is employed to cultivate Bacillus pasteurei, and a stirring method was adopted for sand solidification. The results demonstrate successful consolidation of desert aeolian sand via MICP. The innovative contribution of this research lies in its potential to improve soil quality and augment the structural integrity of vast desert aeolian sand deposits in China, offering promising prospects for sustainable engineering applications.